Discussion of the requirements for water sample collection and preservation in GB/T 5750.1–5750.13–2023 "Standard Examination Methods for Drinking Water" - Juan FEI; Yang YU; Zhen DING; Hao ZHENG (Zhongguo gonggong weisheng)
Collecting and preserving water samples are critical steps in water quality analysis. Proper methods of sample collection and preservation are prerequisites for obtaining accurate water quality analysis results. The "Standard Examination Methods for Drinking Water" (GB/T 5750.1–5750.13–2023) came into effect on October 1, 2023, and serves as the primary reference for conducting the collection and preservation of drinking water samples. GB/T 5750.2 specifies the basic requirements and principles for collecting and preserving water samples, while GB/T 5750.4–5750.13 outlines the specific requirements for collecting and preserving water samples for various indicators. This article, based on GB/T 5750.2 and GB/T 5750.4–5750.13, summarizes the sample collection and preservation requirements for various water quality indicators and test methods, and compiles the sample collection and preservation requirements for routine and comprehensive analytical indicators of drinking water quality. It also examines issues related to the duration of water sample preservation and the addition of preservatives, with the aim of providing references for relevant institutions conducting on-site water quality monitoring.